Evaluating the Safety Profile of Propofol Sedation in Patients Undergoing Endoscopic Variceal Band Ligation: A Comprehensive Analysis - Shahzad, Arslan; Ramzan, Minahil; Tahir, Muhammad; Tahir, Muhammad Zuhair; Tahir, Muhammad Zubair; Shahzad , Muhammad Babar (Journal of Rawalpindi Medical College, 2024)
Objective: To find out the incidence of complications of Endoscopic Variceal Band Ligation, when done under Propofol sedation. Methods: This was a retrospective observational study, which was conducted in the Gastroenterology department, PAF Hospital. From 1st Feb 2019 to 30th June 2023. Patients who underwent Endoscopic Variceal Band Ligation were included in the study. Anesthesia was provided using Propofol and Midazolam. Endoscopic variceal band ligation was carried out by a consultant gastroenterologist. Incidence of complications during the procedure and within 48 hours was noted. Results: Out of 385 patients included in the study, re-bleeding was reported in 8 patients (2.1%), bacteremia in 8 patients (2.1%), hypotension in 77 patients (20%), and hypoxia in 56 patients (14.5%). The rest of the complications such as perforation, Mallory-Weis tear, cardiac arrhythmias, and myocardial infarction were not observed in any patient. Conclusion: Propofol is a safe drug for deep sedation during Endoscopic Variceal Band Ligation associated with reduced complication risk.